Advanced practice in nursing and the allied health professions - McGee, Paula (Chichester, England : Wiley-Blackwell, 2009)
Advanced Practice in Nursing and the Allied Health Professions enables nurses and members of allied health professions to effectively diagnose and treat patients, in a wide variety of settings. It is especially relevant in regions where access to other health providers is limited.
1. Development of Advanced Nursing Practice in the United Kingdom / Paula McGee -- 2. UK Health Policy and Health Service Reform / Alistair Hewison -- 3. Advanced Practice in Allied Health Professions / Paula McGee and David Cole -- 4. Conceptualisation of Advanced Practice / Paula McGee -- 5. Advanced Assessment and Differential Diagnosis / Paula McGee -- 6. Prescribing and Advanced Practice / Sue Shortland and Katharine Hardware -- 7. Advanced Practice in Dietetics / Linda Hindle -- 8. Advanced Practice in Occupational Therapy / Lynne Frith and Janette Walsh -- 9. Working as an Advanced Nurse Practitioner / Mark Radford -- 10. Pioneering New Practice / Kate Gee -- 11. Cultural Competence in Advanced Practice / Paula McGee -- 12. Leadership in Advanced Practice: Challenging Professional Boundaries / Sally Shaw -- 13. Management Issues in Advanced Practice / Paula McGee and Mark Radford -- 14. Preparation of Advanced Practitioners / Paula McGee -- 15. Careers of Advanced Practitioners / Chris Inman and Paula McGee -- 16. International Perspective of Advanced Nursing Practice / Madrean Schober -- 17. Future for Advanced Practice / Paula McGee.
Includes bibliographical references and index.
Keywords: Nurse practitioners